PENDEKATAN SISTEM DALAM PERENCANAAN PENDIDIKAN DI SD NEGERI SUNGAI MIAI 11 - Oktavia, Amalia; Zubaidah, St; Sulistiyana; Suhaimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of a systems approach in educational planning at Sungai Miai 11 Public Elementary School. The systems approach views educational planning as a process involving various interrelated components, such as students, educators, curriculum, facilities and infrastructure, and the school environment. This study uses a qualitative method with a descriptive approach. Data were obtained through interviews, observations, and documentation with the principal, teachers, and parties involved in the preparation of educational planning. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of a systems approach in educational planning at Sungai Miai 11 Public Elementary School has helped the school integrate input, process, and output aspects in a more structured manner. This has an impact on planning that is more focused and effective and supports the continuous improvement of educational quality.